How does a missing part become important for primary school students in understanding fractions? - Pramudiani, Puri; Herman, Tatang; Turmudi; Dolk, Maarten; Doorman, Michiel (Journal on Mathematics Education, 2022)
Understanding of fractions is difficult for Indonesian students. This often leads to misinterpretation in solving fractional problems. In this study, a task aiming at identifying students’ struggles in understanding the basic concept of part-whole relationships in fractions was developed and tested with six 4th-grade students. The task uses Indonesian sweet food, martabak, that has a rounded pizza-like shape as a context in which one slice was missing. Realistic Mathematics Education underlies the context designed, that was also inspired by the Dutch textbook Alles telt Q Basiswerkschrift. The study used a qualitative methodology through an interview, observation, and written test. The result of this study indicated that the students’ struggles can be identified as follows: making references to the whole, making references to the complete partition, and making sense of the incomplete partition. The study showed that the designed tasks have potentials to provoke students' reasoning in learning fractions. The findings indicate that when students learn fractions, their understanding of the meaning of fractions should be well addressed with problems that challenge this part-whole relationship. Challenging this relationship can be supported with problems that have some ambiguity about what is the ‘whole’ using the missing part context.